Análisis del impacto financiero de la exoneración de impuesto a la renta para sociedades nuevas establecidas en el COPCI en la Provincia del Guayas periodo 2011 – 2015 - Vélez Luna, Nadia Carolina (2016)
Tax incentives are constituted in legal measures that grant favorable treatment to certain taxpayers based on reasons of public interest, equity and social justice, with the publication of the Organic Code of Production, Trade and Investment – COPCI in 2010 the exemption was granted in the payment of income tax for new companies that generate assets in the economy and invest in transcendental activities for the change of the productive matrix in Ecuador. Guayas province ranks second place at the national level in the development productive activities, so the present research aims to analyze the financial impact of income tax exemption in new societies established in the province of Guayas from the publication of the Copci, through a descriptive study, with longitudinal section and panel design in which information submitted to the Tax Administration on companies which availed of this benefit in the period 2011 to 2015 will be analyzed and the application financial analysis techniques. As a result it was found that only 0.49% of companies incorporated from 2011 and were eligible to benefit, they did; in them it can be evidenced that its financial behavior is lower than the average of the sectors to which they belong according to the reports of the Superintendency of Companies, additionally simulations were carried out through the @ Risk software with 90% probability it showed that the proposed exemption in the law does not reach the expected financial impact, since during the early years of the start of effective operation in the absence of the exemption savings for the payment of income tax is not material.